PENGARUH MODEL PEMBELAJARAN PASAR TEHADAP HASIL BELAJAR PPKn SISWA KELAS VIII SMPN 1 PUSAKO KECAMATAN PUSAKO KABUPATEN SIAK - Lia Permana; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low student learning outcomes of PPKn at SMPN 1 Pusako. The formulation of the problem in this study is "is there any influence of the use of Market learning models on learning outcomes whether students in class VIII SMPN 1 Pusako?". This study aims to determine the effect of the use of Crossword Puzzle learning models in improving the learning outcomes of PPKn grade VIII SMPN 1 Pusako. This research was conducted at SMPN 1 Pusako in August 2018. This research is a quantitative descriptive research that was experimental. The population in this study were students of class VIII SMPN 1 Pusako. The sample in this study was taken based on "Random Sampling" technique. where the classes taken into the sample were students of class VIII.2 (experimental class) who were given a market learning model, and class VIII.3 (control class) were students who were given conventional methods. Then the data were analyzed using homogeneity test and "t" test. The subject matter that is applied is the "Norms and Justice". Based on the results of the study indicate that there is an influence of learning outcomes between students who use Market models and conventional methods in SMPN 1 Pusako this can be seen from the results (>). Thus there is an effect of the use of Market learning models on student learning outcomes VIII. The magnitude of the effect after being calculated with a gain test shows the market learning model gives an effect on learning outcomes of 0,40 in the medium category. Where there was an increase in the average learning outcomes of the experimental class to 79,25 and the average increase in the learning outcomes of the control class was 54,07.Key Words : Market, Learning Outcomes